Mentoring, educational preferences, and career choice: Evidence from two field experiments in Bhutan - Ryotaro Hayashi; Hyuncheol Bryant Kim; Norihiko Matsuda; Trinh Pham (Asian Development Bank (ADB), 2024)
We use data from two separate randomized control trials to examine whether career mentoring influences the educational preferences and career choices of Bhutanese students in grades 10 and 12. These mentoring programs provide information on technical and vocational education and training (TVET) for grade 12 students and science, technology, engineering, and mathematics (STEM) education systems for grade 10 students; labor market outcomes; and mentors' experiences in each field. Despite the contrasting levels of recognition and stigma associated with TVET and STEM, both programs are generating greater interest among students, as indicated in their stated preferences. While there are also positive changes in the mindset and attitudes of students in grades 10 and 12, the increased interest does not translate into increased applications and enrollments. We interpret these findings as supporting the importance of nonmonetary factors in shaping educational decision-making.
Keywords: I23; I24; J4; J24; 330; STEM; TVET; career mentoring; education choices; Bhutan